Qualitative flood risk assessment for road and railway infrastructures: the experience of the MOVIDA project - N. Petruccelli; L. Mantecchini; A. Gallazzi; D. Molinari; M. Hammouti; M. Zazzeri; S. Sterlacchini; F. Ballio; A. Brath; A. Domeneghetti (Proceedings of the International Association of Hydrological Sciences, 2024)
The Po River District Authority promoted the MOVIDA project with the aim to define appropriate methodologies for flood risk assessment and being compliant with the European Floods Directive (Directive 2007/60/EC). A dedicated Open Source Geographic Information System (i.e. QGIS geoprocessing modules) has been developed for mapping the expected damages in all areas at significant risk in the Po District (Northern Italy), considering five categories of exposed elements (population, infrastructures, economic activities, environmental and cultural heritage, and na-tech sites). Focusing on road and railway infrastructures, the methodology proposed within the project adopts information coming from different data sources (Regional Geoportals, Open Street Map, etc.) and allows to qualitatively estimate the potential risk associated with a flood event. Different risk classes (High, Medium, Low and Null) are assigned in relation to roads category (i.e., Highways, Main, Secondary, Service, Other) or railways type (High-Speed train or not), thus considering both the relevance of the infrastructure itself (as well as its topographical characteristics: e.g. tunnel, bridge, etc.) and the magnitude of the expected event (i.e., hazard). The definition of the risk matrix led to the estimation of the lengths of the sections exposed to different risk levels, which is useful to support the definition of potential mitigation measures and support the competent bodies in the organization of the rescue.